2008
DOI: 10.1111/j.1467-6281.2007.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated With Going‐Concern‐Modified Audit Opinions: An Analysis of the Australian Audit Market

Abstract: This article examines the potential costs to Australian auditors and their clients from the issuance of first‐time going‐concern‐modified audit opinions. We examine the population of Australian companies receiving a first‐time going‐concern‐modified audit opinion during the period 1994–97 and a matched sample of financially distressed firms receiving a clean audit opinion. Results indicate that auditor switching is positively associated with receipt of a going‐concern‐modified opinion. However, we find no empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
5
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 26 publications
6
60
5
6
Order By: Relevance
“…This discovery has been documented in studies on auditor switching in the United Kingdom (Craswell, 1988;Lennox, 2000), Australia (Carey, Geiger, & O'Connell, 2008), China (Chan, Lin, & Mo, 2006), Belgium (Vanstraelen, 2003) and the US (Carcello & Neal, 2003;Chow & Rice, 1982;Geiger, Raghunandan, & Rama, 1998;Smith, 1986). This offers strong empirical support to the idea that auditor dismissal poses a potential economic threat when the auditor is considering a modified report on a going concern basis.…”
Section: Auditor Switchingmentioning
confidence: 84%
See 2 more Smart Citations
“…This discovery has been documented in studies on auditor switching in the United Kingdom (Craswell, 1988;Lennox, 2000), Australia (Carey, Geiger, & O'Connell, 2008), China (Chan, Lin, & Mo, 2006), Belgium (Vanstraelen, 2003) and the US (Carcello & Neal, 2003;Chow & Rice, 1982;Geiger, Raghunandan, & Rama, 1998;Smith, 1986). This offers strong empirical support to the idea that auditor dismissal poses a potential economic threat when the auditor is considering a modified report on a going concern basis.…”
Section: Auditor Switchingmentioning
confidence: 84%
“…Some studies examine the relationship between the opinion in the report and the client firm's decision to sack the auditor. The majority of studies at international level found that auditors are more likely to be dismissed a year after issuing a report with an opinion modified by going-concern concerns (Carcello & Neal, 2003;Carey et al, 2008;Chow & Rice, 1982;Craswell, 1988;Geiger et al, 1998;Lennox, 2000;Smith, 1986;Vanstraelen, 2003).…”
Section: Auditor Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Este control ha sido implementado en estudios posteriores que proporcionan la evidencia más robusta de la que se dispone. Sin embargo, mientras que Pryor y Terza (2002), Vanstraelen (2003), Gaeremynck y Willekens (2003) encuentran resultados favorables, Carey et al (2008) concluyen que no existen indicios para pensar en la existencia de un efecto profecía.…”
Section: El Informe De Auditoría Como Profecía Autorrealizada Revisiunclassified
“…Así, mientras algunos de ellos aportan evidencia consistente con el mismo (Pryor y Terza, 2002;Vanstraelen, 2003;Gaeremynck y Willekens, 2003), otros no encuentran asociación alguna entre tipo de opinión y probabilidad de quiebra (Citron y Taffl er, 1992Carey et al, 2008), llevando a argumentar que este fenómeno es más un mito que una realidad. La evidencia contradictoria unida a la difi cultad metodológica que supone contrastar empíricamente si la opinión actúa como una profecía que tiende a realizarse hace que existan todavía aspectos que deben ser sometidos a investigación.…”
Section: Introductionunclassified